Design, fabrication and evaluation of a plantain roaster. (2012)
Roasted plantain (boli) is a delicacy in Nigeria. The conventional method of processing this food is crude, stressful and unhygienic. In this work, an electric roaster capable of roasting twenty-one plantain fingers per batch was designed, fabricated and tested. The roaster had two electric heating elements (one at the top and the other at the base of the roaster) supplying power at the rate of 2.4 kW In addition, moisture release pipe and a temperature regulator were incorporated. The roaster was used to produce plantain, product was compared with roasted plantain prepared using the conventional method to test acceptability. At a p < 0.05 significance level, it was observed that the samples had no significant difference in appearance, aroma, texture and overall acceptability. However, sample at the upper layer of the roaster was significantly different from the other samples in taste. Generally, sample roasted in the lower part of the roaster was most preferred.